Postdigital storytelling - Jordan, Spencer, author.
1 online resource.
Keywords: "Postdigital Storytelling offers a groundbreaking re-evaluation of one of the most dynamic and innovative areas of creativity today: digital storytelling. Central to this reassessment is the emergence of metamodernism as our dominant cultural condition. This volume argues that metamodernism has brought with it a new kind of creative modality in which the divide between the digital and non-digital is no longer binary and oppositional. Jordan explores the emerging poetics of this inherently transmedial and hybridic postdigital condition through a detailed analysis of hypertextual, locative mobile and collaborative storytelling. With a focus on twenty-first century storytelling, including print-based and non-digital art forms, the book ultimately widens our understanding of the modes and forms of metamodernist creativity. Postdigital Storytelling is of value to anyone engaged in creative writing within the arts and humanities. This includes scholars, students and practitioners of both physical and digital texts as well as those engaged in interdisciplinary practice-based research in which storytelling remains a primary approach"--